3D stress intensity factors for weld toe semi-elliptical surface cracks using XFEM. (July 2016) - Pang, John H.L.; Tsang, Kin Shun; Hoh, Hsin Jen
Abstract: Stress intensity factor and weld toe magnification factor solutions have been developed for T-butt joint geometries using the three-dimensional extended finite element method to model a semi-elliptical weld toe crack in a fillet-welded T-butt joint plate. The stress intensity factors of the semi-elliptical surface crack in a plain plate under tension were in good agreement with the reference solution by Newman and Raju cited in BS 7910 standard. The effect of the fillet welded T-butt joint over the stress intensity factor solution for a semi-elliptical surface crack in a plain plate are presented as a series of weld-toe magnification factors. The new magnification factor solutions were curve-fitted to upper bound, mean and lower bound solutions for practical use in a fatigue life prediction model. The predictions were verified by comparison to available fatigue life data, as well as the commonly used weight function technique. Fatigue crack growth modelling of weld toe semi-elliptical surface cracks were investigated for initial surface cracks with crack depth to plate thickness ratio ( a/T ) of 0.01 and three different crack aspect ratio ( a/c ) of 0.25, 0.5 and 1.0. Highlights: Stress intensity factor solutions were developed for T-butt geometries. Weld toe magnification solutions presented as upper bound, mean and lower bound. Practical weld toe magnification factor solutions were developed. Effect of crack depth to plate thickness on fatigue crack growth was investigated.